Borrelia spirochetes in European exotic farm animals - Hrnková, Johana; Golovchenko, Marina; Musa, Abubakar Sadiq; Needham, Tersia; Italiya, Jignesh; Ceacero, Francisco; Kotrba, Radim; Grubhoffer, Libor; Rudenko, Natalie; Cerný, Jirí (Frontiers in Veterinary Science, 2022)
Ticks transmit a broad spectrum of pathogens, threatening both animal and human health. Tick survival and proliferation are strongly dependent on host selection and suitability. The hard tick Ixodes ricinus, which is widespread throughout most of Europe, is a host generalist capable of feeding on many different vertebrate species. Pasture-kept exotic farm animals may be at a high risk for tick and tick-borne pathogens infestations but research characterizing this is currently lacking. This study focused on the detection of Borrelia spirochetes (including Borrelia miyamotoi) in exotic farm animals. Using nested-PCR with Borrelia-specific primers, 121 serum samples from 54 exotic farm animals of several species bred in four different farms in Bohemia and Moravia (Czechia) were tested. Positive samples were sequenced for the identification of Borrelia species. The prevalence of Borrelia DNA in the samples ranged from 13% to 67%, depending on the sampling site. The sequencing results confirmed the DNA presence of multiple spirochete species from the Borrelia burgdorferi sensu lato complex. Only one sample from an ostrich (Struthio camelus) was found to be positive for Borrelia myiamotoi. The results show that exotic farm animals can serve as hosts for hard ticks and can be infected by Borrelia spirochetes, transmitted by hard ticks. Therefore, these animals could play a relevant role in maintaining Borrelia spirochetes in nature.